Penggunaan Media Pembelajaran Kahoot Berbasis Game Based Learning Untuk Meningkatkan Hasil Belajar Siswa Pada Materi Ikatan Kimia - Laumbo, Nirwana; Saiya, Abdon; Kumajas, Jenny (General Chemistry Journal, 2024)
The purpose of this research is to determine student learning outcomes after using Kahoot learning media based on game based learning on chemical bonding material. This research is quantitative research using the Quasi Experimental Design method with a Posttest-Only Control Design. This research was conducted in class XI IPA 2 and XI IPA 5 SMA Negeri 1 Airmadidi in the 2023/2024 academic year as an experimental class and a control class with 27 students each. Data collection uses learning outcomes tests, namely posttests after carrying out the learning process. The research data obtained was the average value of student learning outcomes (posttest) in the experimental class was 73.81 and the control class was 62.70. Before carrying out the t-test, a normality and homogeneity test was first carried out, it was found that the data was normally and homogeneously distributed. The results of the t test obtained at the significant level α = 0.05, namely tcount = 2.88 > ttable= 1.67, meaning that H0 is rejected and Ha is accepted, where Ha is the average learning outcome of students who use Kahoot learning media based on game based learning which is greater than students who use lecture and assignment methods. Thus, it can be concluded that student learning outcomes in chemical bonding material increased after using the Kahoot learning media based on game based learning.